A study of pregnancy birth and mortality rate in colonial narrative and sacred narrative in Sabah from the 1940s to 2017 - Pakri, Mohamad Rashidi Mohd; Openg, Elizabeth Joanny (2017)
A community is defined by its unique ness of traditions and customs, which have been passed down from one generation to another. Among community members, the traditions and customs of the community must be upheld as they are the pride of the community and they indicate the roots of the community